Pengaruh Model Pembelajaran TGT (Teams Games Tournament) Terhadap Hasil Belajar Tenis Meja - Dony Andrijanto (Indonesian Journal of Physical Education and Sport Science, 2023)
The success of the learning process depends on the educator, where an educator plays an important role in the learning process. The learning paradigm so far considers the learning process only centered on educators. Along with the development of the world of education, this paradigm changes to a learning process that is no longer teacher-centered, but student-centered. One way to solve this problem is to use instructional media that are appropriate to the characteristics of students. This study aims to determine the effect of learning media on the learning outcomes of forehand strokes in table tennis games. The method used in this research is quasi-experimental research with one group pretest posttest design. The population used in this study were students in MTS Sunan Giri class VIII the sample used was 36 students. The research will be conducted 4 times. The data collection technique used was a table tennis forehand test. The analysis technique used is descriptive analysis, normality test and hypothesis testing. Based on the results of the analysis, the results of the hypothesis test were 0.00, which means <0.05. Through these results it can be concluded that there is a significant influence of learning media on the learning outcomes of forehand strokes in table tennis games.